Association of -34 T > C CYP17 Gene Polymorphism with Benign Prostatic Hyperplasia in Babylon Province, Iraq - Abdulsamie H. Altaee (Journal of Global Pharma Technology, 2018)
Benign prostatic hyperplasia (BPH) is the most common benign tumor in men, and its incidence is age-related. This study aims to investigate the effect of -34 T > C CYP17 gene polymorphism on BPH susceptibility and clinical progress.Fifty males patients with BPH clinically diagnosis attended to Al-Hillah Teaching Hospital, as well as fifty males apparently healthy control in a case-control study were subjected to present study. The -34 T > C CYP17 gene polymorphism was detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique.Genetic analysis of -34 T > C CYP17 gene polymorphism shows a significantly higher difference when comparing patients with the control groups. The dominant and codominant models of -34 T > C CYP17 gene polymorphism were shown significant change when compared with healthy control The T/C-T/T is genotyping responsible and related to the risk of BPH.In conclusion, -34 T > C CYP17 gene polymorphism could have an important role in the development and pathogenesis of BPH.Kewords: Benign prostatic hyperplasia, CYP17 gene polymorphism, PCR-RFLP, Babylon, Iraq.